Financial mathematics of pension funds using entry age normal and projected unit credit methods - Maysarah, Maysarah; Husein, Ismail (Universitas Islam Negeri Raden Intan Lampung, 2024)
ASN is an abbreviation for State Civil Apparatus. ASN is a term for professions that work under the auspices of government agencies at both the central and regional levels. This regulation of rights and obligations is a form of state intervention in the regulation of ASN. In implementing the AAUPB (general principles of good government) ASN Law, it was found that there were differences in the rights and obligations of PNS and PPPK. According to Article 21 of the ASN Law, civil servants have the right to receive salaries, allowances, holidays, old age security, protection, and increased qualifications. Meanwhile, according to Article 22, PPPK has the right to receive salary allowances, holidays, protection, and competency development. A very significant difference in the rights that PPPK does not receive is pension and old-age security. Based on this law, this research aims to provide a general overview of the pension calculations that will be received by PPPK using the EAN and PUC methods, so that of these two methods, which method is better for the number of normal contributions and actuarial obligations for participants and agencies between EAN and PU? Based on the calculation results, the method PUC (Project Unit Credit) is more suitable to use because there is no significant difference between normal contributions and actuarial obligations, so it can be profitable for both parties.